Penerapan Integrated Marketing Communication pada Penjualan Produk Beras Lokal Tabanan dalam Menghadapi Dominasi Merek Nasional - Saputra, Gede Arya Dandi; Suparna, Putu (Pusat Riset dan Inovasi Nasional, 2026)
This research aims to explore how Integrated Marketing Communication (IMC) is applied to enhance the sales performance of local rice products in the midst of competition with well-established national brands. Intensified competition arises due to the increasing presence of rice products from other regions as well as premium national brands that offer added value. These market dynamics underscore the importance of strategic marketing communication, especially in designing messages, selecting appropriate media channels, and applying the right consumer engagement approach to strengthen brand awareness and loyalty.A descriptive qualitative method was employed, utilizing a case study approach on a local rice producer in Tabanan Regency. Data collection involved in-depth interviews, field observations, and documentation related to promotional and sales activities, which were then analyzed through data reduction, data display, and conclusion-drawing stages.The results demonstrate that the coordinated use of IMC elements such as advertising, sales promotion, public relations, digital marketing, and word-of-mouth has contributed significantly to improving brand perception and market competitiveness. Ultimately, this study suggests that adopting a consistent and well-structured IMC strategy is essential for local rice producers to sustain their presence and achieve growth amidst the dominance of national rice brands.